2002
DOI: 10.1034/j.1600-0897.2002.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Expression Pattern of Cytokines in Semen of Men with Genital Infection and Oligo‐Terato‐Asthenozoospermia

Abstract: The measurement of each cytokine separately in the SP of men with INF-OTA, in spite of the existing significant differences, does not have a diagnostic value in male infertility. However, a combined determination of IL-6, IL-8, IL-11 in the SP of men with genital infection and oligo-terato-asthenozoospermia may provide clinically useful information for the diagnosis of male accessory gland infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 22 publications
2
44
0
1
Order By: Relevance
“…Controversy exists as to whether elevated cytokine levels are related to semen quality. Previous studies suggested that elevated cytokine levels were not related to semen quality (Comhaire et al, 1994;Dousset et al, 1997;Matalliotakis et al, 1998;Eggert-Kruse et al, 2001;Matalliotakis et al, 2002), although more recent studies have supported such a relationship (Furuya et al, 2003;Kopa et al, 2005). The advantage of the present study is that it is the first to specifically investigate levels of both IL-6 and IL-8 in semen from C trachomatis-infected and -noninfected patients.…”
Section: Discussionmentioning
confidence: 87%
“…Controversy exists as to whether elevated cytokine levels are related to semen quality. Previous studies suggested that elevated cytokine levels were not related to semen quality (Comhaire et al, 1994;Dousset et al, 1997;Matalliotakis et al, 1998;Eggert-Kruse et al, 2001;Matalliotakis et al, 2002), although more recent studies have supported such a relationship (Furuya et al, 2003;Kopa et al, 2005). The advantage of the present study is that it is the first to specifically investigate levels of both IL-6 and IL-8 in semen from C trachomatis-infected and -noninfected patients.…”
Section: Discussionmentioning
confidence: 87%
“…In man, there has been extensive interest in seminal plasma cytokine profile, which has been characterised for IL-1a/b, IL-2, IL-4, IL-6, IL-8, IL-10, IL-11, IL-12, tumour necrosis factor (TNF)-a/b, IFN-a/g, TGF-b1, RANTES, CSF-1, G-CSF, macrophage-CSF, stem cell factor, monocyte chemotactic and activating factor, macrophage migration inhibitory factor and vascular endothelial growth factor as well as an array of their soluble receptors (Naz & Stanley 1995, Shimoya et al 1995, Frenette et al 1998, Fujisawa et al 1998a,b, Matalliotakis et al 1998a,b, 2002, Omu et al 1998, Huleihel et al 1999, Naz & Leslie 2000, Maegawa et al 2002, Gutsche et al 2003, Paulis et al 2003, Basu et al 2004. However, these studies have been limited in the array of cytokines investigated in individual patients, and their focus has principally been on the association of these inflammatory mediators with a variety of disorders resulting in male factor infertility and/or characterised by inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators previously demonstrated that 90K enhances generation of cytotoxic effector cells (Ulrich et al, 1994) as well as the secretion of IL-1, IL6, and tumor necrosis factor alpha (Powell et al, 1995). As those and other interleukins (IL-8 and IL-11) involved in the inflammatory reaction to tissue damage caused by infection (Comhaire et al, 1999) were previously observed to be increased in the ejaculate of patients with male accessory gland infection compared to controls (Alexander et al, 1998;Matalliotakis et al, 2002), a comparable increase of seminal 90K compared to controls could be expected in our patients. However, our finding of comparatively lower seminal 90K in patients is not surprising if we hypothesize that patients with male accessory gland infection harbor a disregulated local immune response.…”
Section: Discussionmentioning
confidence: 99%